2023
DOI: 10.3389/fphar.2023.1258403
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing tylosin dosage for co-infection of Actinobacillus pleuropneumoniae and Pasteurella multocida in pigs using pharmacokinetic/pharmacodynamic modeling

Eon-Bee Lee,
Muhammad Aleem Abbas,
Jonghyun Park
et al.

Abstract: Formulating a therapeutic strategy that can effectively combat concurrent infections of Actinobacillus pleuropneumoniae (A. pleuropneumoniae) and Pasteurella multocida (P. multocida) can be challenging. This study aimed to 1) establish minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), time kill curve, and post-antibiotic effect (PAE) of tylosin against A. pleuropneumoniae and P. multocida pig isolates and employ the MIC data for the development of epidemiological cutoff (ECOFF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…These findings confirmed our initial hypothesis that the PK of gentamicin could be affected by the health status of the animals. Because our earlier comparative studies with tylosin, a macrolide antibiotic, also demonstrated significantly lower exposure (C max and AUC 24h ) and shorter T 1/2 values in co-infected pigs compared to healthy pigs [37], we assume this phenomenon to be common to several classes of antimicrobial agents. The clinical significance of these differences is, however, dependent on several factors.…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirmed our initial hypothesis that the PK of gentamicin could be affected by the health status of the animals. Because our earlier comparative studies with tylosin, a macrolide antibiotic, also demonstrated significantly lower exposure (C max and AUC 24h ) and shorter T 1/2 values in co-infected pigs compared to healthy pigs [37], we assume this phenomenon to be common to several classes of antimicrobial agents. The clinical significance of these differences is, however, dependent on several factors.…”
Section: Discussionmentioning
confidence: 99%